2020
DOI: 10.1001/jamanetworkopen.2020.29917
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Survival in Patients With Autoimmune Disease

Abstract: Key Points Question Is there an association between autoimmune disease and lung cancer survival? Findings This cohort study of 349 patients compared lung cancer survival in those with autoimmune disease with that of patients without it and observed no difference in overall survival, even when broken down by locoregional and distant stage. No one subtype of autoimmune disease was associated with worse survival compared with that of the control cohort, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…For instance, cancer patients with formerly diagnosed AIDs are often undertreated with respect to their malignancy. The major reason for this insufficient treatment is “poor initial performance status or frailty” ( 136 ). An increased frequency of leukopenia due to the simultaneous use of immunosuppressive and chemotherapeutic drugs in these patients is a possible reason for shorter anti-cancer treatment periods or lower doses of anti-cancer drugs.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, cancer patients with formerly diagnosed AIDs are often undertreated with respect to their malignancy. The major reason for this insufficient treatment is “poor initial performance status or frailty” ( 136 ). An increased frequency of leukopenia due to the simultaneous use of immunosuppressive and chemotherapeutic drugs in these patients is a possible reason for shorter anti-cancer treatment periods or lower doses of anti-cancer drugs.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Another single-center study revealed no significant difference in OS in patients with lung cancer with and without autoimmune disease. 27 Compared with the single-center studies, we used a larger sample size taken from a national cohort and investigated a larger number of specific autoimmune conditions. 26 , 27 An earlier study using the SEER Medicare cohort found no association between autoimmune disease and increased mortality in patients with lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Compared with the single-center studies, we used a larger sample size taken from a national cohort and investigated a larger number of specific autoimmune conditions. 26 , 27 An earlier study using the SEER Medicare cohort found no association between autoimmune disease and increased mortality in patients with lung cancer. Nevertheless, compared with our study, that study had a shorter minimum lookback period to identify patients with autoimmune disease and did not breakdown their survival analysis by specific autoimmune condition.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, a large and retrospective study conducted from 2003 to 2019 confirms that the survival of lung cancer patients who also have a rheumatic disease (n = 177) is not inferior to the cohort without such comorbidities (n = 219). [13] This was true for OS, DFS, and the rate of recurrence of locoregional disease. Of concern was the fact that more patients with the autoimmune disease did not receive standard of care.…”
Section: International Journal Of Molecular and Immuno Oncologymentioning
confidence: 94%